Analysis of delayed training effects in the preparation of the West german water polo team for the 1988 Olympic Games - Hohmann, A. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
This study investigated the variations in the timescale of adaptation to endurance training using the German national water polo players preparing for the Fifth World Championships in 1986. Regression analysis was used on the training and performance data collected, and this highlighted the fact that four players peaked from endurance training in the days immediately prior to the championships whereas four others peaked after the championships. A repeat analysis performed on these players in preparation for the 1988 Olympic Games produced similar results, thus verifying the stability of this training adaptation.